Análise da percepção do público sobre conteúdos de divulgação científica em Ciências Biológicas veiculados em diferentes plataformas midiáticas - Santos, André Luiz Tirollo dos (Universidade Federal de São Carlos, 2021)
This study aims to analyze the effectiveness of different media strategies used in the dissemination of scientific works produced by Brazilian researchers, determining whether these are being effective in transmitting the knowledge generated by the authors of the works in a faithful and instigating way. For this, four scientific dissemination contents in biological sciences were selected, written and published by Facebook and Instagram pages that were not officially related to any research institution, that were not part of large media conglomerates and that had a significant number of followers. Then, a questionnaire was applied to the public participating in the research to assess their perception of the different scientific dissemination materials in question. Finally, the answers provided by the public were forwarded to the authors of the published academic papers so that they could assess whether the information about their work – such as the methodology used, the results obtained and the conclusion of the study – were faithfully transmitted by the media. The data collected through this study showed that the volunteer public had difficulties in answering which methodologies were used in each of the studies published by the scientific dissemination contents addressed. Furthermore, it was evident that a large part of the public did not know how to precisely differ the results of a study and its conclusions.
Analysis of public perception of scientific dissemination content in Biological Sciences broadcast on different media platforms
Keywords: Biologia; Ciência; Mídia digital; Biology; Science; Digital media; CIENCIAS BIOLOGICAS